(untitled) (Brazilian Journal of Radiation Sciences, 2015)
In the case of an accident in a nuclear power plant with radionuclide releases to the environment, members of the public with possible internal contamination with radioactive isotopes of iodine should be screened to identify cases where a more detailed evaluation and medical follow-up is necessary. Screening of large numbers of the public can be performed with a quick measuring protocol using hand held unshielded NaI based detectors giving results in cps. The screening geometry was simulated using the Monte Carlo code Visual Monte Carlo. The results show that for a geometry with the NaI detector near the skin in front of the thyroid, the interference of the gamma radiation coming from other radionuclides released in the accident either deposited in the lung or in the whole body is sufficiently low to allow thyroid screening criteria to be established. The screening criteria were developed using 5, 10 and 15 year old hybrid phantoms and for the adult male based on the ICRP reference voxel phantom.